In premature infants there is no decrease in 24‐hour posttransfusion allogeneic red blood cell recovery after 42 days of storage. Issue 2 (29th November 2017) - Nalbant, Demet; Cancelas, José A.; Mock, Donald M.; Kyosseva, Svetlana V.; Schmidt, Robert L.; Cress, Gretchen A.; Zimmerman, M. Bridget; Strauss, Ronald G.; Widness, John A.
Abstract : BACKGROUND: Critically ill preterm very‐low‐birthweight (VLBW) neonates (birthweight ≤ 1.5 kg) frequently develop anemia that is treated with red blood cell (RBC) transfusions. Although RBCs transfused to adults demonstrate progressive decreases in posttransfusion 24‐hour RBC recovery (PTR24 ) during storage—to a mean of approximately 85% of the Food and Drug Administration—allowed 42‐day storage—limited data in infants indicate no decrease in PTR24 with storage. STUDY DESIGN AND METHODS: We hypothesized that PTR24 of allogeneic RBCs transfused to anemic VLBW newborns: 1) will be greater than PTR24 of autologous RBCs transfused into healthy adults and 2) will not decrease with increasing storage duration. RBCs were stored at 4°C for not more than 42 days in AS‐3 or AS‐5. PTR24 was determined in 46 VLBW neonates using biotin‐labeled RBCs and in 76 healthy adults using 51 Cr‐labeled RBCs. Linear mixed‐model analysis was used to estimate slopes and intercepts of PTR24 versus duration of RBC storage. RESULTS: For VLBW newborns, the estimated slope of PTR24 versus storage did not decrease with the duration of storage (p = 0.18) while for adults it did (p < 0.0001). These estimated slopes differed significantly in adults compared to newborns (p = 0.04). At the allowed 42‐day storage limit, projected mean neonatal PTR24 was 95.9%; for adults, it was 83.8% (p = 0.0002). CONCLUSIONS: These data provide evidence that storage duration of allogeneic RBCs intended for neonates can be increased without affecting PTR24 . This conclusion supports the practice of transfusing RBCs stored up to 42 days for small‐volume neonatal transfusions to limit donor exposure.